Konsep Kewirausahaan Pada Petani Melalui Pendekatan Structural Equation Model (SEM) - ARISENA, GEDE MEKSE KORRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.1, Januari 2016, 2016)
Abstract Agricultural development in Indonesia, had highs and lows life of farmers who receive the effects of policies of the time. In General, farmers seem to always be in a position that is weak and marginalized by the different strategies that are often not impartial and did not have a significant impact on improving the quality of life. During development, farmers must have business relations in the field of agriculture. Entrepreneurship is necessary because every person has the potential to develop a disampinng that everyone has needs that is constantly growing, so everyone will try to implement it as soon as possible. Where farmers should have the motivation, courage to take risks, innovate and managerial competencies that generate entrepreneurial perspective. Method of structural equation modeling (SEM) is suitable to use to solve complex problems, run by agribusiness and science in general business in particular. Structural equation modeling (SEM) is a combination of factor analysis, analisais signs, correlation analysis and multiple regression analysis. Structural equation modeling (SEM) has different characteristics as ordinary regression. Regression usually indicate a causal relationship between observed variables (observed variables), and the structural equations modeling (SEM), also possible causality between unobserved variables (unobserved variables) or tongs are often called hidden variables. Measurement of latent variables in multiple regression error measurement (measurement errors) that affect the measurement bias in an objective point and size variance. Keywords: Entrepreneurship and Structural equation modeling (SEM)